Surgical data science for next-generation interventions - Maier-Hein, Lena; Kenngott, Hannes Götz; Schoch, Nicolai; Wagner, Martin (Nature biomedical engineering, 2017)
Interventional healthcare will evolve from an artisanal craft based on the individual experiences, preferences and traditions of physicians into a discipline that relies on objective decision-making on the basis of large-scale data from heterogeneous sources.